2020
DOI: 10.1016/j.jsv.2020.115335
|View full text |Cite
|
Sign up to set email alerts
|

Special issue: Recent advances in Acoustic Black Hole research

Abstract: Reduction of undesirable structural vibrations and of the associated structure-borne noise is a classical problem that remains important today. There are many ways of passive damping of structural vibrations. Unfortunately, most of them require addition of substantial amounts of damping materials, which is not always possible because of the mass and volume restrictions associated with structures' operational requirements. In this connection, development of new methods of vibration damping is always desirable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Up to now, from the perspective of structural acoustic design, a lot of achievements have been made in reducing the vibration of the base structure and hull structure of the underwater vehicle equipment by setting variable-thickness plates locally. When the one-dimensional or two-dimensional plate structures [1][2][3][4] whose thickness varies according to the power function attenuation law with the exponent of power function of no less than 2 are used locally, the vibration characteristics of structures such as box structures 5,6 , raft structures 4 , and equipment bases 7 are studied by finite element analysis method, or the influence of structural parameters and structural forms of variable-thickness plates on the vibration reduction effect of target structures is analyzed by comparison between structural vibration tests and theoretical studies [8][9][10] . Both of them have concluded that variable-thickness plates can reduce the high-frequency vibration in the target structure.…”
mentioning
confidence: 99%
“…Up to now, from the perspective of structural acoustic design, a lot of achievements have been made in reducing the vibration of the base structure and hull structure of the underwater vehicle equipment by setting variable-thickness plates locally. When the one-dimensional or two-dimensional plate structures [1][2][3][4] whose thickness varies according to the power function attenuation law with the exponent of power function of no less than 2 are used locally, the vibration characteristics of structures such as box structures 5,6 , raft structures 4 , and equipment bases 7 are studied by finite element analysis method, or the influence of structural parameters and structural forms of variable-thickness plates on the vibration reduction effect of target structures is analyzed by comparison between structural vibration tests and theoretical studies [8][9][10] . Both of them have concluded that variable-thickness plates can reduce the high-frequency vibration in the target structure.…”
mentioning
confidence: 99%